2010
DOI: 10.1111/j.1479-828x.2010.01246.x
|View full text |Cite
|
Sign up to set email alerts
|

Over expression of HSP70 and HSF1 in endothelial cells during pre-eclamptic placental stress

Abstract: The over expression of HSP70 and HSF1 seen in the pre-eclamptic endothelial cells suggests its possible protective role as stress specific natural adaptive response against the generated stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The increased expression of HSF1 in endothelial cells from term PE suggests a possible protective role as stress specific natural adaptive response against the generated stress [75,76]. CRH, CYP11A1, TEAD3 showed an increased DNAm in preeclamptic placentas, suggesting a hormonal involvement in PE [25].…”
Section: Role Of Dna Methylation In the Pathophysiology Of Pementioning
confidence: 90%
“…The increased expression of HSF1 in endothelial cells from term PE suggests a possible protective role as stress specific natural adaptive response against the generated stress [75,76]. CRH, CYP11A1, TEAD3 showed an increased DNAm in preeclamptic placentas, suggesting a hormonal involvement in PE [25].…”
Section: Role Of Dna Methylation In the Pathophysiology Of Pementioning
confidence: 90%
“…Hsp70 represents an antioxidative stress marker. The overexpression of Hsp70 and the heat shock transcription factor (Hsf1) seen in the pre-eclamptic endothelial cells suggests its possible protective role as stress-specific natural adaptive response against the generated stress30. As proposed by Molvarec et al 15, we hypothesise that haemodynamic stress, oxidative stress (placental or systemic), placental ischaemia, ischaemia of other organs as well as maternal systemic inflammatory response may contribute to the overexpression of Hsp70, resulting in elevated circulating Hsp70 levels.…”
Section: Discussionmentioning
confidence: 65%
“…Studies have demonstrated that oxidative stress is one of the key factor in complicating preeclampsia which results in preterm birth (Padmini et al 2009b;Padmini & Lavanya, 2011;Padmini & Lavanya, 2009a). The first line of defense for oxidative stress is not sufficient enough to combat with the generated stress.…”
Section: Discussionmentioning
confidence: 99%
“…HSP70 chaperones regulate important physiological processes such as cell cycle, cell differentiation and programmed cell death (Mayer & Bukau, 2005;Cobreros et al 2008). The over expression of HSP70 in relation to the oxidative stress generated in preeclamptic condition suggest their protective role in stress management prolonging the cell survival in the placental endothelial cells during preeclampsia (Padmini et al 2009b;Padmini & Lavanya, 2011).…”
Section: Introductionmentioning
confidence: 99%